(untitled) (Religious dialogue and cooperation, 2021)
Starting from the assumption that religious identification has increased its significance in the shaping of identity in the environments which have been in the ambience of “frozen conflict” on a long-term basis, the extent of significance ascribed to it by students in Kosovo & Metohija has been examined. It is assumed that, independently of how the students themselves identify regarding religion, and of the place of religious identification in the identity matrix, they manifest significant distance towards the religiously “other” because it is the area with the politicization of the church and religious feelings, whereas religion becomes a means, an instrument of empowering national identity. The importance of religious affiliation as an identity segment of the surveyed population has been seen through the comparison of selfassessments of the importance of a series of identity markers (both those regarding traditional identity structures such as national, religious and family affiliation, and the markers typical of modern identity, such as sub-cultural, professional and regional affiliation). Religious/confessional distance was examined on the Bogardus scale, adapted to the examined student population. The research was conducted by the survey technique in December 2016/January 2017 on the proportional quota sample of 997 students of the Albanian University in Priština and the Serbian state University in Kosovska Mitrovica. The research was aimed at measuring the value of religious/confessional distance of the students at these universities and exploring the importance of religion/confession in the structure of their identity.